Benign Neglect or Active Destruction? A Critical Analysis of Refugee and Informal Sector Policy and Practice in South Africa - Crush, Jonathan; Skinner, Caroline; Stulgaitis, Manal (African Human Mobility Review, 2021)
To fully comprehend the disabling policy environment in which refugees in SouthAfrica attempt to carve out a livelihood, it is important to analyse two largelyindependent but overlapping streams of policy-making. This paper firstexamines the post-apartheid refugee protection regime and traces how and whya generous right-based approach has been progressively comprised by growingrestrictionism, exclusion and bureaucratic ineptitude. The 2017 RefugeesAmendment Act and White Paper on International Migration represent theculmination of this process. While both are probably unimplementable and willbe the subject of numerous court challenges, they can be seen as a major retreatand an increasing failure to protect. The second part of the paper traces thehistory of national and municipal informal sector governance since the early1990s. Since so many refugees are forced or choose to work informally, theuncertainty and confusion this history has produced is of particular relevance.Refugee entrepreneurs have regularly been the victims of general and targetedinformal sector eradication campaigns.